Art-based interventions for women’s mental health in pregnancy and postpartum: A meta-analysis of randomised controlled trials - Qian, Jialu; Sun, Shiwen; Wang, Man; Sun, Xiangyu; Yu, Xiaoyan (Frontiers in Psychiatry, 2023)
Objective: Pregnant and postpartum women are vulnerable to psychological problems with a high estimated prevalence. To date, there is no meta-analysis that specifically assesses the effectiveness of art-based interventions to improve mental health in pregnant and postpartum women. The objective of this meta-analysis was to assess the efficacy of art-based interventions when delivered to pregnant and postpartum women. Methods: Systematic literature searches were conducted from the inception to 6 March 2022 in seven English databases, including PubMed, Embase, Cochrane Central Register, CINAHL, ProQuest, Scopus, and Web of Science. Randomized controlled trials (RCTs) reporting art-based interventions targeting the improvement of women’s mental health in pregnancy and postpartum were included. Cochrane risk of bias tool was applied to assess evidence quality. Results: Twenty-one randomized controlled trials (RCTs) involving 2815 participants were eligible for data analysis. A pooled analysis demonstrated that art-based interventions significantly reduced anxiety (SMD = -0.75, 95% CI=-1.10 to -0.40) and depression symptoms (MD = -0.79, 95% CI=-1.30 to -0.28). However, art-based interventions did not alleviate stress symptoms as expected in our findings. Subgroup analysis demonstrated that intervention implementation time, intervention duration and music selected by the participants vs. not could have influence on the efficacy of art-based intervention for anxiety. Conclusion: In perinatal mental health, art-based interventions may be effective in alleviating anxiety and depression. In the future, we still need to conduct high-quality RCTs to validate our findings and enrich clinical application of art-based interventions.